PENERAPAN AKAD IJARAH MUNTAHIYA BITTAMLIK (IMBT) DI BANK BRI SYARIAH KCP JOMBANG - Nadya Uswatun Chasanah; Dunyati Ilmiah; Arivatu Ni’mati Rahmatika (STIE Bakti Bangsa Pamekasan, 2020)
As the ijarah contract develops, the ijarah contract is modified to become the Muntahiyah Bittamlik Ijarah contract, which is a lease agreement that ends with ownership. In reality this IMBT is rarely applied by Islamic banks, whereas in the context of diversification of financing products, this agreement is deemed necessary to be optimized for implementation. This research uses a descriptive analytical type of field research. Equipped with library research and content analysis by comparing the existing rules in the DSN MUI Fatwa with existing practices at BRI Syariah KCP Bank Jombang. The results of this study are the compatibility between DSN MUI about Ijarah Muntahiya Bittamlik with the practice of the Ijarah Muntahiya Bittamlik contract at BRI Syariah Syariah Bank Jombang. This conformity includes fatwa no. 71 / DSN-MUI / VI / 2008 concerning Sale and Lease Back, No. 09 / DSN-MUI / IV / 2000 concerning ijarah financing, No. 56 / DSN-MUI / V / 2007 concerning the provisions of the Ujrah review on LKS, No. 27 / DSN-MUI / III / 2002 concerning al-Ijarah al-Muntahiya Bittamlik, No. 89 / DSN-MUI / XII / 2013 concerning Islamic refinancing.